2009
DOI: 10.1111/j.1365-3164.2009.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of feline dermatophytosis in a shelter: a field study

Abstract: Enzootic dermatophytosis in a shelter with approximately 140 cats was treated according to a protocol combining identification, isolation and treatment of subclinical carrier and affected animals in accordance with a three-area system: healthy animals (no lesions and negative cultures), subclinical carrier animals (no lesions but with positive cultures) and clinically affected animals (lesions and positive cultures). The cats were examined and inspected under a Wood's lamp and had samples taken for fungal cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
2
26
1
2
Order By: Relevance
“…Dermatophytosis is an important consideration when sheltering cats from any source because it is highly contagious, has zoonotic potential, and can be difficult to diagnose and to treat (Carlotti et al, 2010). Its management is particularly challenging when sheltering large numbers of seized cats, because of the potential transmission of Microsporum canis in temporary shelters to both cats and to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatophytosis is an important consideration when sheltering cats from any source because it is highly contagious, has zoonotic potential, and can be difficult to diagnose and to treat (Carlotti et al, 2010). Its management is particularly challenging when sheltering large numbers of seized cats, because of the potential transmission of Microsporum canis in temporary shelters to both cats and to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an isolation and quarantine facility is important in the control of infectious diseases in shelters [35][36][37]. Most respondents had some form of isolation facility; however 26.2% and 17% had none, for dogs and cats respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a 21‐day course of itraconazole (10 mg/kg orally once daily) and twice weekly lime sulphur cured all cats by day 49 2 . In a recently published French study, cats treated with 0.2% enilconazole (Imaverol ® ) twice weekly and oral itraconazole, 5 mg/kg once daily every other week, were all cured by day 56 7 . Another evaluation of the efficacy of systemic antifungal therapy alone reported that cats treated with itraconazole (10 mg/kg orally once daily) cured in 56 days 8 .…”
Section: Discussionmentioning
confidence: 99%